Respuesta :
Answer: X=3
Explanation:2x-5(x-4)=-9+4x=8
2x-5x+20=-9+4x+8
2x-5x-4x=-9-20+8
-7x/-7=-21/-7
x=3
Answer:
X=3
Explanation:
Let's solve your equation step-by-step.
2x−5(x−4)=−9+4x+8
Step 1: Simplify both sides of the equation.
2x−5(x−4)=−9+4x+8
2x+(−5)(x)+(−5)(−4)=−9+4x+8(Distribute)
2x+−5x+20=−9+4x+8
(2x+−5x)+(20)=(4x)+(−9+8)(Combine Like Terms)
−3x+20=4x+−1
−3x+20=4x−1
Step 2: Subtract 4x from both sides.
−3x+20−4x=4x−1−4x
−7x+20=−1
Step 3: Subtract 20 from both sides.
−7x+20−20=−1−20
−7x=−21
Step 4: Divide both sides by -7.
−7x
−7
=
−21
−7
x=3
Answer:
x=3